"Am I Doing Enough?" Special Educators' Experiences with Emergency Remote Teaching in Spring 2020 - Rachel K. Schuck; Rachel Lambert (MDPI AG, 2020)
While the COVID-19 pandemic radically changed all aspects of everyone's life, the closure of schools was one of the most impactful, significantly altering daily life for school personnel, students, and families. The shift to Emergency Remote Teaching (ERT) presented particular challenges to special educators of students with significant support needs who often benefit from strong interpersonal connections, modeling, and the use of physical manipulatives. This paper details the experiences of two elementary special education teachers as they navigated the transition to ERT. The teachers reported three distinct stages of ERT: making contact, establishing routines, and transitioning to academics. They also discussed the challenges they faced during this period, such as the inequity in resources amongst their students, needing to rely on at-home support in order to meaningfully teach students, and changes in what it meant to be a teacher while having to teach online. While clearly not in favor of online learning, the teachers do present glimmers of hope, for example, with regards to increased communication between teachers and parents. The challenges and strategies used to overcome these challenges will be of use to educators in the coming months, with implications for distance learning in this population.